EFFECT OF BLENDED LEARNING APPROACH ON SECONDARY SCHOOL STUDENTS’ INTEREST IN BIOLOGY IN AWKA EDUCATION ZONE (UNIZIK Journal of STM Education, 2024)
This study investigated the effect of blended learning approach on secondary school students’ interest in Awka Education Zone. Two research questions guided the study and three hypotheses were tested. The research adopted quasi-experimental non randomized pre-test post-test control group design. The population consisted of 1842 (810 males and 1032 females) Senior Secondary II Biology students from four intact classes of two public co- educational secondary schools inAwka Education Zone of Anambra State. The sample for the study consisted 103 SS II Biology students (42 males and 61 females) obtained through multi stage sampling procedure Students' interest in Biology Questionnaire (SIBQ) was the instrument for data collection. This instrument was validated and tested for reliability with reliability coefficient being 0.83, using Cronbach Alpha method. The research questions were answered using mean and standard deviation while the hypotheses were tested at 0.05 level of significance using Analysis of Covariance (ANCOVA). The findings of the study showed significance effect of Blended Learning Approach on Students’ interest in Biology. This implies that blended learning approach is capable of enhancing interest in Biology. However, result showed gender influence on Students interest in Biology when blended learning approach was used as a method of instruction but there was no significant interaction between instructional approach and gender on interest. It was recommended among others that blended learning approach should be incorporated in teaching of sciences especially Biology in senior secondary schools.
Keywords: Blended learning, interest, biology, gender